TO ANY MATH HELPERS

posted by .

Pleeeese help!

Use the substitution method to solve each linear system:

-x+3y+1=0
3x-y+1=0


4x-3y=-13
-2x+y=4

Please help, thanks:):)!!!!

  • TO ANY MATH HELPERS -

    1)

    x= -.5
    y= -.5

    2)

    x=.5
    y=5

  • TO ANY MATH HELPERS -

    1.
    from the 1st equation: x = 3y+1
    into the 2nd:
    3(3y+1) - y +1 = 0
    9y + 3 - y +1 = 0
    8y = -4
    y = -1/2
    sub into 2nd:
    3x - (-1/2) + 1 = 0
    3x = -3/2
    x = -1/2

    Do #2 the same way
    from the 2nd: y = 2x+4
    etc

    (Just stating the answers is not acceptable and serves no purpose)

  • TO ANY MATH HELPERS -

    Oh thank you to both helpers!!! I have understood how to do it now:)

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. math

    Use a substitution method to solve the linear system 2a=8 a+b=2
  2. algebra 1

    use the substitution method to solve the linear system. 9x+6y=3 3x-7y=-26 please show me an example of how to do it.
  3. algebra

    Requesting help. (I must reckon, that X is a variable, and y is y-intercept) Q: Try to use the substitution method to solve the the linear system y=3x an y=3x-7. What do you notice?
  4. maths

    use the substitution method to solve the linear system. 1. 3x=9 -x+2y=9 3x/3 = 9/3 x = 3 -x(3)+2y = 9 -3+2y = 9 2y = 12 y = 6 is (3,6) correct?
  5. Linear Equations

    Can you please help solve this equation using the substitution method?
  6. Algebra

    Use substitution method to solve the linear system. Can someone please check if I did this problem right?
  7. Algebra

    Use the substitution method to solve the linear system. 1/8p+3/4q=7 3/2p-q=4 Thanks.
  8. Math 2 questions

    Use the substitution method to solve each linear system: -x+3y+1=0 3x-y+1=0 4x-3y=-13 -2x+y=4 Please help, thanks:):)!!!!
  9. math

    If it says use the method of substitution to solve the system of linear equations 3a=6-b 3a=4-b How do i find the solution
  10. Math

    17) solve this linear system using the method of substitution. 2y-x=-10 y= -3/2x-1 20) simplify then solve by substitution 2(x-4)+y=6 3x-2(y-3)=13 just need help with these 2.

More Similar Questions